THE POTRAIT OF HUMAN ANXIETY IN IAN MCEWAN’S ATONEMENT - Ricki Alfredo Bintang (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study explores the phenomenon of anxiety in Ian McEwan's Atonement (2001), focusing on neurotic and moral anxiety. Using a qualitative research method, it examines the characters and their psychological dynamics through the novel's text and relevant journals. The study employs Freud's psychoanalytic theory to understand the internal conflicts faced by the characters. Data collection involved in-depth exploration of the novel and analysis of literature on anxiety. The findings reveal that the portrayal of anxiety in Atonement reflects the complexities of neurotic and moral anxiety, influencing the main character's actions and decisions. The character's neurotic anxiety, stemming from her inability to grasp reality, interacts with moral anxiety related to her responsibilities. This representation highlights the struggle with deep anxiety and its effects on interpersonal relationships and the search for meaning. The study aims to provide insights into how anxiety shapes individual identity and morality within a broader narrative context.